Successful Cultivation of Lac in Banaras Forest Division, Uttar Pradesh - Bhatia, C. L. (Indian Forester, 1956)
The article reviews the work of lac cultivation done since 1951, in Banaras Forest Division, on the recommendation made to Government of Uttar Pradesh by the Indian Lac Research Institute, Namkum, Ranchi. It also touches, in general, on various other aspects of lac cultivation. The work was started during the hot weather of 1951 when only 1,000 trees were pruned, for infection the same year during November. There are about 18,000 trees under lac cultivation to-day. As the entire enterprise remained a losing concern during the first 2 years, probably due to inexperience, it was decided to stop departmental cultivation and to get the work done through a contract or on payment of annual premia and royalty. Nobody came forward to take this up on a royalty basis and departmental work was continued. Adjustments were made to cut down expenses and profits were recorded during 1953-54 for the first time. Lac cultivation has provided jobs to a considerable number of men and women of all categories. As the area under cultivation can be increased manifold, the problem of unemployment can be solved to some extent. Method of cultivation, figures of expenditure and revenue and adjustments made through experience have been given in detail. Recommendations and suggestions are made as to the nature and extent of work to be done in future.